Understanding mobile payment in Malaysian Entrepreneurial Ecosystems: A scientometric analysis of adoption patterns - Mustapha, Musramaini; Kader, Mohd Aidil Ridua Awang; Mohd Pauzi, Nooradzlina; Ab Malik, Ariff Md (Journal of Islamic, Social, Economics and Development, 2025)
The global adoption of mobile payment systems has seen significant growth, but the uptake among entrepreneurs varies significantly across different regions. This study examines mobile payment adoption among Malaysian entrepreneurs, analyzing trends and patterns from 112 Scopus-indexed papers. Key factors influencing adoption are categorized by year, affiliations, authors, and subject areas. The findings indicate that research in this field is on the rise in Malaysia, with incremental yearly increases: 19 publications in 2021, 20 in 2022, and 35 in 2023. Moreover, clusters like continuance adoption and mobile payment systems remain prominent. This research provides insights into the adoption of digital payments in emerging nations, offering valuable data for entrepreneurs, technology providers, and business owners aiming to leverage mobile payment technologies for business growth. It highlights the growing relevance of mobile payments for entrepreneurial success, contributing to the broader understanding of digital transformation in Malaysia's entrepreneurial landscape.